2016
DOI: 10.3390/ijerph13090895
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Dust Exposure and Respiratory Disorders among Textile Workers at a Textile Company in the Southern Part of Benin

Abstract: The textile industry sector occupies a prominent place in the economy of Benin. It exposes workers to several occupational risks, including exposure to cotton dust. To assess the effect of exposure to cotton dust on the health of workers, this study was initiated and conducted in a Beninese cotton industry company. The objective of the study was to evaluate the respiratory disorders among the textile workers exposed to cotton dust and the cross-sectional study involved 656 subjects exposed to cotton dust and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 29 publications
2
29
0
6
Order By: Relevance
“…It is important to note that, along with PM 2.5 and BC, individuals may be exposed to a range of individual or combined airborne pollutants including vapors, gases, dusts, fumes, fibers, and mists (VGDFFiM) at varying daily intensities . Certain jobs, such hairdressers and farm and textile workers, and their associated occupational exposures are strongly associated with cough, wheeze, and nasal symptoms, including nasal discharge and frequent sneezing . However, studies have focused on general sinonasal symptoms and environmental exposures without clear clinical diagnosis and characterization of CRS using mostly self‐reported symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that, along with PM 2.5 and BC, individuals may be exposed to a range of individual or combined airborne pollutants including vapors, gases, dusts, fumes, fibers, and mists (VGDFFiM) at varying daily intensities . Certain jobs, such hairdressers and farm and textile workers, and their associated occupational exposures are strongly associated with cough, wheeze, and nasal symptoms, including nasal discharge and frequent sneezing . However, studies have focused on general sinonasal symptoms and environmental exposures without clear clinical diagnosis and characterization of CRS using mostly self‐reported symptoms.…”
mentioning
confidence: 99%
“…10 Certain jobs, such hairdressers and farm and textile workers, and their associated occupational exposures are strongly associated with cough, wheeze, and nasal symptoms, including nasal discharge and frequent sneezing. 11,12 However, studies have focused on general sinonasal symptoms and environmental exposures without clear clinical diagnosis and characterization of CRS using mostly self-reported symptoms. Those studies lacked objective measures of inflammation or the amount of occupational exposures and its impact in disease severity.…”
mentioning
confidence: 99%
“…Occupational exposures have been related to adult-onset asthma and work-aggravated asthma, and the population-attributable fraction is estimated at about 15% [2]. Several jobs and occupational exposures are strongly associated with cough, wheeze, and nasal symptoms [36], and low socioeconomic status is associated with asthma, cough, and wheeze [7]. In population-based studies, occupational exposure to vapours, gas, dust, and fumes (VGDF) have been shown to increase the risk of asthma [8], respiratory symptoms [9] and rhinorrhoea [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in occupational epidemiology are based on specific workforces or exposure to specific agents [3,6,1113]. In large population-based studies, occupational exposures are commonly assessed by using a job-exposure matrix (JEM) based on job title, or by using a single-item question of exposures to VGDF.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis is partly confirmed by papers from Africa and Asia (but important health and safety challenges are still clearly present in Europe and Australia as other papers in the issue demonstrate). The study by Hinson et al reveals how exposures to ‘old’ and well-known hazards continue to present risks and cause diseases in new populations of textile workers in countries such as Benin where occupational health research in many respects is nascent [3]. …”
mentioning
confidence: 99%